Inequality as a Construct of Customary Law: Access to Home Ownership Rights of Women in Lampung - Napsiah, Napsiah; Muryanti, Muryanti; Wijayanti, Yani Tri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The current study examined the challenges of women living under Lampung’s highly stringent customary law pertaining to the acquisition of home ownership rights in 3 villages in Hulu Sungkai, North Lampung, Indonesia. In Lampung customary law, the home is conferred to the male descendant. This study employed the constructivist perspective and used data collected from field observations, interviews, document analyses, and literature reviews to address the practices of traditional power among Lampung women. The research results indicate that the construct of customary law has positioned women and men differently, subsequently leading to unequal treatment of women in the family. Patriarchy’s dominance in Lampung customary law has made life more difficult for women, who are already responsible for housekeeping and enriching education. Still, customary practices provide them no opportunity of any kind, and this has negative consequences. Women are highly dependent on men, and women frequently become victims of domestic violence. The construct of Lampung customs has established how women are treated in society. Lampung’s customary construct needs to be counterbalanced by a better public understanding of property ownership laws so that people have more gender awareness regarding home ownership.